Design of graded materials by particle reinforcement during accumulative roll bonding - Schmidt, Christian; Ruppert, Mathis; Höppel, Heinz Werner; Nachtrab, Frank; Dietrich, Anja; Hanke, Randolf; Göken, Mathias (Advanced Engineering Materials, 2012)
Graded distributions of copper particles in ultrafine-grained aluminium sheets are produced by accumulative roll bonding and particle reinforcement. The metallic copper particles are sprayed on the sheet surfaces under variation of spray distance and/or relative velocity of the spray gun to the sheet. Therewith, the particle content could be varied by a factor of three. After solutionizing, the successful gradation is clearly proven by tensile tests showing a steady and monotonous gradient along the rolling direction. By a systematic analysis of the spraying process, the particle content profile is calculated. Accuracy of the calculation is confirmed by electrical resistivity measurements. The presented method enables the production of tailored sheets by graded particle reinforcement. The graded sheets are also used for basic investigation of materials properties along graded compositions.
WW1::920

Global and local strain rate sensitivity of bimodal Al-laminates produced by accumulative roll bonding - Ruppert, Mathis; Schunk, Christopher; Hausmann, Daniel; Höppel, Heinz Werner; Göken, Mathias (Acta Materialia, 2016)
Laminated metallic composites of 5 mm thickness, with a bimodal grain size distribution and alternating layers of commercial purity aluminum (Al99.5) and high purity aluminum (Al99.999) were successfully processed by accumulative roll bonding at room temperature up to 8 cycles. With increasing number of ARB cycles the layers of commercial purity aluminum become ultrafine-grained, whereas the grain size in the high purity aluminum remains clearly above 1 extgreekmm. The mechanical properties of the laminates were investigated by compression testing with strain rate jumps and by nanoindentation using continuous stiffness method and nanoindentation strain rate jump tests. Thereby the strain rate sensitivity was determined both globally, proving the bulk laminate material, and locally, proving the single layers of the laminate. It was found that the local strain rate sensitivity of the ultrafine-grained Al99.5-layers is increasing up to 4 ARB cycles, while the local strain rate sensitivity of the coarse grained Al99.999-layers remains rather constant independently of the number of cycles. In contrast to that, the global strain rate sensitivity of the bulk laminate increases up to 8 cycles without saturation. Thermally activated annihilation of dislocations at the grain boundaries and interfaces between the coarse grained and ultrafine-grained layers is proposed in order to interpret the findings.
WW1::1056
Keywords: Nanomaterials

Influence of cross-rolling on the mechanical properties of an accumulative roll bonded aluminum alloy AA6014 - Ruppert, Mathis; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2014)
Sheets of aluminum AA6014 (AlMgSi) were successfully accumulative roll bonded from T4 condition up to eight cycles. Using the conventional ARB route, processing was on the one hand performed at room temperature. On the other hand, sheets were pre-heated in a furnace for 2.5 min at 210 °C prior to each rolling step. Besides the conventional ARB route an ARB cross-rolling route, where the rolling direction is rotated around 90° after each cycle, was used at room temperature. For all three processing conditions an ultrafine-grained microstructure was obtained. Due to a change in strain path, the ultimate tensile strength and the yield strength of the cross-rolled AA6014 exceed those of the samples processed by conventional ARB. However, a strong decrease in terms of elongation to failure is visible after 6–8 cycles of ARB compared to the pre-heated ARB sheets. Fracture analysis reveals necking of individual layers for the samples processed at room temperature. Therefore, after 7 cycles of cross-rolling at RT, one last cross-rolling step at elevated temperature was performed in order to improve bonding quality. This leads to a high strength of about 475 MPa and a satisfactory elongation to failure of about 10%.
WW1::999

Influence of upscaling accumulative roll bonding on the homogeneity and mechanical properties of AA1050A - Ruppert, Mathis; Böhm, Wolfgang; Nguyen, H.; Höppel, Heinz Werner; Merklein, Marion; Göken, Mathias (Journal of Materials Science, 2013)
Accumulative roll bonding (ARB), as a method for production of ultrafine grained materials, is frequently supposed to be easily transferable to established industrial production lines. In literature, however, common sheet dimensions used for ARB in a laboratory scale are between 20 and 100 mm in width. In order to quantify the potential of upscaling the ARB process to a technological relevant level, sheets of AA1050A with an initial sheet width of 100–450 mm were accumulative roll bonded up to 8 cycles. In this regard, three different rolling mills of distinct dimensions were used for processing of the sheet material. The influence of process parameters and the reproducibility of the process, in terms of mechanical properties and homogeneity of the sheets, were studied by means of mechanical and microstructural characterization. Both appear to be largely independent on the sheet size and the rolling mill utilized for production. Only small deviations after the first cycles could be detected, vanishing in subsequent cycles due to the features of microstructural evolution. The finally obtained results indicate a high potential for industrial application of ARB and illustrate the possibility to upscale the process to a level necessary for that purpose.
WW1::970

Mechanical properties of copper/bronze laminates: Role of interfaces - Ma, Xiaolong; Huang, Chongxiang; Moering, Jordan; Ruppert, Mathis; Höppel, Heinz Werner; Göken, Mathias; Narayan, Jagdish; Zhu, Yuntian (Acta Materialia, 2016)
Interfaces play a crucial role in mechanical behaviors of both laminated and gradient structured materials. In this work, copper/bronze laminates with varying interface spacing were fabricated by accumulative roll bonding and subsequent annealing to systematically study the interface effect on mechanical properties. Heterogeneities exist in chemical composition, grain size, hardness and texture across the interfaces. Simultaneous improvement of strength and ductility with decreasing interface spacing is found in tensile tests. Extra geometrically necessary dislocations (GNDs) are found to accumulate in the vicinity of interfaces, which is due to mechanical incompatibility across the interfaces. Importantly, an interface-affected zone spanning a few micrometers was found, which is not affected by interface spacing. These observations suggest the existence of an optimum spacing, which may produce the highest hardening capacity and ductility without sacrificing strength. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Interface; Laminate structure; Geometrically necessary dislocation (GND); Interface-affected zone; Back stress hardening

Mechanical properties of ultrafine-grained AlZnMg(Cu)-alloys AA7020 and AA7075 processed by accumulative roll bonding - Ruppert, Mathis; Strebl, Michael; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2015)
Ultrafine-grained AA7020 (AlZnMg) and AA7075 (AlZnMgCu) were produced by accumulative roll bonding (ARB) with up to 6 cycles. Different pre-heating treatments and their effect on the mechanical performance of the materials were investigated by means of hardness measurements and uniaxial tensile testing. It was found for AA7020 that by pre-heating at 230 degrees C for 2.5 min prior to each rolling step, an UTS of 550 MPa can be achieved, which is 51 % higher compared to the peak-aged T6 reference. For AA7075, pre-heating at 280 degrees C for 2.5 min leads to a very high UTS of 720 MPa after four ARB passes. A negative strain rate sensitivity was found for both alloys, which shifts toward zero with increasing number of ARB cycles. Post-ARB heat treatment was performed in order to overcome the reduced ductility after ARB. This leads to an enhanced strain hardening capacity after 4 cycles, resulting in an increase of the uniform elongation from 1.4 to 2.0 % for AA7020 and from 0.9 to 2.1 % for AA7075.

Tailored heat treated accumulative roll bonded aluminum blanks: failure under bending stresses - Nguyen, H.; Boehm, W.; Tsoupis, Ioannis; Göken, Mathias; Höppel, Heinz Werner; Schmidt, Christian; Hausöl, Tina; Ruppert, Mathis; Merklein, Marion (Production Engineering, 2016)
Ultrafine-grained accumulative roll bonded (ARB) sheet metals of aluminum alloys have a high potential for lightweight construction. The mechanical properties can be enhanced regarding strength and ductility by the combination of ARB and a local heat treatment according to the Tailor Heat Treated Blanks technology. The present investigation focuses on the failure behavior of ultrafine-grained ARB blanks. Due to the low formability of these high-strength ARB metals, a detailed understanding of the failure mechanisms is essential. For this purpose, an established approach to determine the different stages of damage of the material for conventional materials is now applied to multilayered aluminum in the as-received and heat-treated condition. In this context, air bending tests are used to qualify and quantify the bending and forming behavior of ARB sheets of AA1050A and AA6016 aluminum alloys.
Keywords: Tailor Heat Treated Blanks (THTB); Ultrafine-grained microstructure (UFG); Failure; Formability; Bending; Accumulative roll bonding (ARB)

Ultrafine-grained austenitic stainless steels X4CrNi18-12 and X8CrMnNi19-6-3 produced by accumulative roll bonding - Ruppert, Mathis; Freund, Lisa; Wenzl, Thomas; Höppel, Heinz Werner; Göken, Mathias (Metals, 2015)
Austenitic stainless steels X4CrNi18-12 and X8CrMnNi19-6-3 were processed by accumulative roll bonding (ARB). Both materials show an extremely high yield strength of 1.25 GPa accompanied by a satisfactory elongation to failure of up to 14% and a positive strain rate sensitivity after two ARB cycles. The strain-hardening rate of the austenitic steels reveals a stabilization of the stress-strain behavior during tensile testing. Especially for X8CrMnNi19-6-3, which has an elevated manganese content of 6.7 wt.%, necking is prevented up to comparatively high plastic strains. Microstructural investigations showed that the microstructure is separated into ultrafine-grained channel like areas and relatively larger grains where pronounced nano-twinning and martensite formation is observed.
WW1::1039